(untitled) (Research, Society and Development, 2021)
To analyze the scientific evidence about nursing care in the screening of breast cancer in patients seen at the Basic Health Unit. This study deals with a bibliographic review of the integrative literature review method, carried out in the months of October and November 2020. A The search was carried out through the VHL, using the databases (LILACS), (MEDLINE), (BDENF), and through the Google Scholar Portal, adhering to the descriptors: “Nursing care” AND “Cancer of Mama ”AND“ Primary Attention ”, combined with the operator“ B ”. It is relevant that the nurse develops actions to face breast cancer, know the methods of early detection and perform screening actions for the previous identification of breast cancer or precursor lesions in asymptomatic individuals as soon as possible, so that effective measures are implemented reducing their mortality. Health professionals must assume the responsibility of participating in the detection of abnormalities in the breast in consultations, thus providing comprehensive, resolutive and humanized assistance. It is essential for nurses to act during consultations regarding women’s health care in detecting these abnormalities through embracement, clinical breast examination, health education and requesting more complex tests when necessary.